Informasi Budaya Suku Karo Sumatera Utara - Sitepu, Septyani Emlita; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
Abstract The writing of this paper aims to describe the process of making information about Karo tribe culture in North Sumatera. Data collected using descriptive research methods with objects of cultural research found in Karo tribes as well as techniques for collecting data through interviews with traditional male, female, and community members, as well as through literature studies in accordance with the discussion under study. Based on the discussion it can be concluded the process of making information about the culture of the North Sumatera tribe as follows: (1) determine the topic: the topic raised was Karo tribe culture. (2) information gathering: data collection on Karo tribe culture was conducted by interview. (3) packaging information: packaging information is carried out in accordance with the draft content that has been made in advance. The design of information content consist of the front cover, preface, table of content, introduction of chapter, contents of the subject of information on the culture of the North Sumatera Karo tribe, and the back cover. Keywords: information; North Sumatera Karo tribe cultureÂ